An efﬁcient forward error correction code for wireless sensor networks - Salah A. Alabady (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
The main requirements in the design of wireless sensor network applications are to minimize energy consumption and maximize battery lifetime. Power is primarily consumed during wireless transmission and reception. Automatic repeat request (ARQ) and forward error correction (FEC) are the two basic methods to recover erroneous packets. As energy conservation is a major issue of concern in wireless sensor networks, repeat transmission because the error in the data received is not an option, and FEC would be preferred over ARQ. FEC is applied in situations where retransmissions are relatively costly or impossible. A successful data transmission means a higher energy saving and a long-life network. This paper presents a novel linear block forward error correction code for wireless sensor network applications called Low Complexity Parity Check (LCPC). The LCPC code offers lower encoding and decoding complexity than other types of codes. To validate the performance of the LCPC code, the proposed coding scheme was investigated at different values of data transmission with different types of modulations over Additive white Gaussian noise (AWGN) and Rayleigh fading channels. The simulation results show that the proposed code outperforms the renowned LDPC (8, 4), (255,175), and (576, 288) codes.